Recentring the Animal in Multispecies Ethnography: Review of John Hartigan, Jr., Shaving the Beasts: Wild Horses and Ritual in Spain - Vaught, Jeannette (Humanimalia, 2024)
Review of: John Hartigan, Jr., Shaving the Beasts: Wild Horses and Ritual in Spain. Minneapolis: University of Minnesota Press, 2020. ix + 304 pp. 54 b&w photos. 24.95 (pb).